Minimising soil organic carbon erosion by wind is critical for land degradation neutrality. Issue 93 (March 2019) - Chappell, Adrian; Webb, Nicholas P.; Leys, John F.; Waters, Cathleen M.; Orgill, Susan; Eyres, Michael J.
Highlights: Soil erosion by wind reduces SOC stocks in addition to slow decomposition to CO2 . Our new dynamic wind erosion scheme is better than LDN static cover metric. We identified global dryland regions where SOC erosion undermines LDN. Abstract: The Land Degradation-Neutrality (LDN) framework of the United Nations Convention to Combat Desertification (UNCCD) is underpinned by three complementary interactive indicators (metrics: vegetation cover, net primary productivity; NPP and soil organic carbon; SOC) as proxies for change in land-based natural capital. The LDN framework assumes that SOC changes slowly, primarily by decomposition and respiration of CO2 to the atmosphere. However, there is growing evidence that soil erosion by wind, water and tillage also reduces SOC stocks rapidly after land use and cover change. Here, we modify a physically-based wind erosion sediment transport model to better represent the vegetation cover (using land surface aerodynamic roughness; that is the plant canopy coverage, stone cover, soil aggregates, etc. that protects the soil surface from wind erosion) and quantify the contribution of wind erosion to global SOC erosion (2001–2016). We use the wind erosion model to identify global dryland regions where SOC erosion by wind may be a significant problem for achieving LDN. Selected sites in global drylands also show SOC erosion by wind accelerating over time. Without targeting and reducing SOC erosion, management practices in these regions will fail to sequester SOC and reduce land degradation. We describe the interrelated nature of the LDN indicators, the importance of including SOC erosion by wind erosion and how by explicitly accounting for wind erosion processes, we can better represent the physical effects of changing land cover on land degradation. Our results for Earth's drylands show that modelling SOC stock reduction by wind erosion is better than using land cover and SOC independently. Furthermore, emphasising the role of wind erosion in UNCCD and Intergovernmental Panel on Climate Change (IPCC) reporting will better support LDN and climate change mitigation and adaptation globally.